Students’ Motivation to Acquire English through Virtual Learning in the Midst Covid-19 Pandemic - Eisha Jamila Qomariyah Ikhwan; Erna Andriyanti (Lingua Cultura, 2021)
The research aimed to find out students’ motivation to acquire English as a foreign language through virtual learning in the midst of Covid-19 pandemic. It involved 202 students spread throughout Indonesia. Data were collected by means of motivation questionnaires adopted from the Situational Motivation Scale (SIMS) of students’ motivation, i.e., instrumental motivation and integral motivation. The data were analyzed with descriptive statistics and Pearson’s Correlation on SPSS 22. The result shows that the students have a low level of motivation both for integrative and instrumental motivation to acquire English. The statistical calculation reveals that there is a correlation between the students’ motivation and virtual learning activity as shown by the level of significance 0,000<0,05 with the coefficient Pearson’s correlation of 0,282. There is no correlation between the students’ motivation and the Covid-19 pandemic as depicted by Pearson’s correlation of 0,062 with the significant level of 0,382>0,05. The research implies a need for a more innovative instructional design for virtual language learning to better improve students’ motivation to learn English during the Covid-19 pandemic.